Implementation of the Cooperative-Reflective Approach Through the Process-Based Writing Model in Teaching Arabic Writing Skills - Selvia Angela; Lailatul Fitri; Umar Faruq; Ahmad Umar Faruq (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2025)
This study aims to analyze the implementation and effectiveness of the Cooperative-Reflective Approach through the Process-Based Writing (PBW) model in teaching maharah kitabah (Arabic writing skills) among students of the Arabic Language Education Department at IAIN Kediri. The research employed a mixed-methods approach using an Explanatory Sequential Design, where quantitative data were first collected through pre-test and post-test to measure writing improvement, followed by qualitative data collection through observation, interviews, and reflective journals to elaborate on the results. The participants consisted of 28 undergraduate students from Class D and one postgraduate tutor. The findings revealed a significant improvement in the average score from 38.21 to 74.82, with a gain of 36.61 points and an effect size of 2.90, indicating a very large influence of the intervention on students’ writing performance. Qualitative results showed that the Cooperative-Reflective approach enhanced students’ active participation, individual responsibility, and reflective awareness in the writing process. Students became more collaborative, critical, and confident in producing coherent and communicative Arabic texts. The study concludes that integrating cooperative and reflective approaches through the PBW model is not only effective in improving maharah kitabah but also contributes to developing a process-based and self-aware Arabic language learning model that aligns with 21st-century higher education demands.